The Use of the Istinbathiyah Method in Learning the Ma’ani (Balaghah) Using Mutasyabihat fi al-Alfadz Verses - Hasim, Muhamad Fuad; Baihaqi, Muhammad; Fatihuddin, Fatihuddin; Mahditama, M. Rajib; Fuadhi, Muhammad Iqbal (Syarif Hidayatullah State Islamic University of Jakarta, Indonesia, 2024)
Balaghah is a branch of Arabic literature that is very important for understanding the meaning of ijaz in the Qur'an. Balaghah is also a science taught in Islamic boarding schools, so it is very important to know the effectiveness of its learning methods. This study aims to determine the effectiveness of the Istinbathiyah method in learning Ma'ani (balaghah). The research method in this study is quantitative with an experimental type. Data collection was carried out by conducting observations, documentation, and tests. Data analysis was carried out statistically, the formula used was the t-test formula or t-test. There are several requirements that must be met before the t-test is carried out, including the Normality test, Homogeneity Test, and Hypothesis Test. The results of this study indicate that the Istinbathiyah method is quite effective with an average value of 16.3 from the control class while 66.9 from the experimental class.